Establishment and validation of an endoplasmic reticulum stress reporter to monitor zebrafish ATF6 activity in development and disease - Eric M. Clark; Hannah J. T. Nonarath; Jonathan R. Bostrom; Brian A. Link (The Company of Biologists, 2020)
Induction of endoplasmic reticulum (ER) stress is associated with diverse developmental and degenerative diseases. Modified ER homeostasis causes activation of conserved stress pathways at the ER called the unfolded protein response (UPR). ATF6 is a transcription factor activated during ER stress as part of a coordinated UPR. ATF6 resides at the ER and, upon activation, is transported to the Golgi apparatus, where it is cleaved by proteases to create an amino-terminal cytoplasmic fragment (ATF6f). ATF6f translocates to the nucleus to activate transcriptional targets. Here, we describe the establishment and validation of zebrafish reporter lines for ATF6 activity. These transgenic lines are based on a defined and multimerized ATF6 consensus site, which drives either eGFP or destabilized eGFP, enabling dynamic study of ATF6 activity during development and disease. The results show that the reporter is specific for the ATF6 pathway, active during development and induced in disease models known to engage UPR. Specifically, during development, ATF6 activity is highest in the lens, skeletal muscle, fins and gills. The reporter is also activated by common chemical inducers of ER stress, including tunicamycin, thapsigargin and brefeldin A, as well as by heat shock. In models for amyotrophic lateral sclerosis and cone dystrophy, ATF6 reporter expression is induced in spinal cord interneurons or photoreceptors, respectively, suggesting a role for ATF6 response in multiple neurodegenerative diseases. Collectively our results show that these ATF6 reporters can be used to monitor ATF6 activity changes throughout development and in zebrafish models of disease. This article has an associated First Person interview with the first author of the paper.